NGC 1883: a neglected intermediate-age open cluster located in the outskirts of the Galactic disc - Carraro, Giovanni (2003)
We report on BVI CCD photometry of a field centred in the region of the open cluster NGC 1883, down to V = 21. This cluster has never been studied so far; we provide, for the first time, estimates of its fundamental parameters - namely radial extent, age, distance and reddening. We find that the cluster has a radius of about 2.5 arcmin, and shows signatures of dynamical relaxation. NGC 1883 is located in the anticentre direction, and exhibits a reddening in the range E(B-V) = 0.23-0.35, depending on the metal abundance. It turns out to be of intermediate age (1 Gyr old), and is quite distant for an open cluster. In fact, it is located 4.8 kpc from the Sun, and more than 13 kpc from the Galactic centre. This results makes NGC 1883 one of the most peripheral old open clusters, with important consequences for the trend of the metallicity with distance in the outer Galactic disc.